Editorial - Lemos Cravo, Pedro Vitor (Fronteira: Journal of Social, Technological and Environmental Science, 2013)
Nesta edição multidisciplinar de "Fronteiras", disponibilizamos artigos que abrangem várias disciplinas, que cursam desde a segurança alimentar até à educação ambiental. In this multidisciplinary issue of “Fronteiras”, we present articles spanning across different subjects, ranging from food security to environmental education.